Polyethylene glycol bowel preparation does not eliminate the risk of acute renal failure: a population-based case-crossover study - Choi, N. K.; Lee, J.; Chang, Y.; Jung, S. Y.; Kim, Y. J.; Lee, S. M.; Lee, J. H.; Kim, J. Y.; Song, H. J.; Park, B. J. (Endoscopy, 2013)
Background and study aims: Polyethylene glycol (PEG) bowel preparations are regarded as effective and safe for colonoscopy; however, recent reports have indicated a risk of acute renal failure (ARF). This population-based case-crossover study evaluated the association between PEG and ARF in screening colonoscopy patients aged ≥ 50 years.Patients and methods: Korean Health Insurance Review and Assessment Service (HIRA) claims data from 1 January 2005 to 31 December 2009 were used in the study. The study population consisted of patients aged ≥ 50 years who were first hospitalized for ARF following colonoscopy involving PEG bowel preparation. For each patient, PEG use in a 1-, 2-, or 4-week period prior to the first hospital admission date for ARF (hazard period) was compared with PEG use in four earlier 1-, 2-, or 4-week control periods. Conditional logistic regression analysis was used to estimate odds ratios (ORs) and 95 % confidence intervals (CIs), adjusting for concomitant medications that could induce ARF. Results: The total number of study patients was 1064 (59 % were male). A greater proportion of patients used PEG during the hazard period than during the control periods (for 4-week time window: 8.8 % vs. 3.2 %). The adjusted ORs for ARF incidence when applying the 1-, 2-, and 4-week periods were 3.1 (95 %CI 2.06 – 4.73), 2.5 (95 %CI 1.76 – 3.53), and 2.1 (95 %CI 1.61 – 4.85), respectively. Conclusions: The use of PEG was associated with the risk of ARF. Adequate hydration and renal function monitoring should be assured before and after colonoscopy, regardless of the bowel preparation regimen used.